Ruptured Aneurysm of the Sinus of Valsalva Causing Pulmonary Embolism: A Rare Association - Barroso, Francisco V. C.; Takakura, Isabela T.; Reis, Ricardo C.; Valente, Acrisio S.; Lima, Neiberg A.; Gomes, Camila R. F.; Justo Neto Júnior, José; Sobrinho, Carlos R. M. Rodrigues (AORTA, 2020)
Aneurysms of the sinus of Valsalva are rare. Unruptured sinus of Valsalva aneurysm is usually asymptomatic and rarely presents as right ventricular outflow obstruction, myocardial infarction as a result of coronary artery compression, conduction disturbances, or endocarditis. They have only been reported as the presumed source of embolism in six cases. We report a patient with right sinus of Valsalva rupture to the right atrium and embolization of aneurysm contents to the pulmonary vasculature.
Keywords: sinus of Valsalva's aneurysm; pulmonary embolism; aneurysm